2018
DOI: 10.1210/js.2018-00269
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Etomidate Infusion for the Management of Severe Cushing Syndrome: Validation of a Standard Protocol

Abstract: ObjectiveDemonstrate the safety and efficacy of a standardized intravenous etomidate infusion protocol in normalizing cortisol levels in patients with severe and life-threatening hypercortisolism.MethodsA retrospective case series of seven patients representing nine episodes of severe hypercortisolism at two large academic medical centers was conducted. Patients were included in this series if they received an etomidate infusion for the treatment of severe and life-threatening hypercortisolism. The etomidate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 22 publications
0
22
0
1
Order By: Relevance
“…In addition to these data, the successful use of a lowdose etomidate protocol has been described recently in an ICU setting. Thus, Carroll et al reported on seven patients with severe CS treated in ICU with a starting dose of 0.02 mg/kg/h of etomidate, which was titrated every 6 h in order to achieve a target cortisol concentration of 275 to 551 nmol/L in 24 to 48 h without the need for cortisol supplementation (8). Patients were given an optional initial 5 mg i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these data, the successful use of a lowdose etomidate protocol has been described recently in an ICU setting. Thus, Carroll et al reported on seven patients with severe CS treated in ICU with a starting dose of 0.02 mg/kg/h of etomidate, which was titrated every 6 h in order to achieve a target cortisol concentration of 275 to 551 nmol/L in 24 to 48 h without the need for cortisol supplementation (8). Patients were given an optional initial 5 mg i.v.…”
Section: Discussionmentioning
confidence: 99%
“…In a seminal article, Schulte et al showed that etomidate given at the dose of 0.30 mg/kg/h was effective in rapidly reducing cortisol levels in patients with CS, while inducing only moderate somnolence (4). Two recent articles confirmed the efficacy and safety of etomidate infusion at these doses in the treatment of severe CS in the intensive care unit (ICU) (7,8). On the other hand, a significant cortisol lowering effect has been demonstrated while using even lower doses of etomidate (0.03 mg/kg/h) (4).…”
Section: Introductionmentioning
confidence: 99%
“…However, intensive care monitoring is necessary, as is regular control of serum cortisol levels [150]. Subsequent studies confirmed this suggestion [151]. Recent studies in patients with Cushing's syndrome who did not require intensive care unit monitoring suggested that they also might benefit from low doses of etomidate [152].…”
Section: Hypercortisolismmentioning
confidence: 99%
“…Etomidate is a parenterally administered anaesthetic agent, which additionally inhibits 11 beta‐hydroxylase, even in subhypnotic doses. It has been used to control severe, life‐threatening hypercortisolism and is particularly helpful as ‘bridge therapy’ to a definitive intervention . Careful monitoring is required to avoid excessive sedation in patients on etomidate therapy.…”
Section: Medical Therapymentioning
confidence: 99%